National Survey of Neonatal Intensive Care Unit Medication Safety Practices - Greenberg, Rachel G.; Smith, P. Brian; Bose, Carl; Clark, Reese H.; Cotten, C. Michael; DeRienzo, Chris (American Journal of Perinatology, 2018)
Objective We conducted a detailed survey to identify medication safety practices among a large network of United States neonatal intensive care units (NICUs).Methods We created a 53-question survey to assess 300 U.S. NICU's demographics, medication safety practices, adverse drug event (ADE) reporting, and ADE response plans.Results Among the 164 (55%) NICUs that responded to the survey, more than 85% adhered to practices including use of electronic health records, computerized physician order entry, and clinical decision support; fewer reported adopting barcoding, formal safety surveys, and formal culture training; 137 of 164 (84%) developed at least one NICU-specific order-set with a median of 10 order-sets.Conclusion Among our survey of 164 NICUs, we found that many safety practices remain unused. Understanding safety practice variation is critical to prevent ADEs and other negative infant outcomes. Future efforts should focus on linking safety practices identified from our survey with ADEs and infant outcomes.
Keywords: neonatal intensive care unit; medication safety practices; adverse drug event; adverse drug event response plan